Study on the effective way to convert waste into resources—game analysis of reverse logistics implementation based on value chain - Zhang, Fengxuan; He, Yixiong (Frontiers in Environmental Science, 2022)
The environmental problems caused by excessive waste discharge are becoming more and more prominent, and how to deal with waste has become a problem that has to be done but is extremely costly. On the other hand, from a value chain perspective, waste has been focused on because of its potential value for conversion. Reverse logistics is an important means of turning waste into resources, solving environmental problems and promoting high-quality development, as well as an important reliance on enriching and improving the value chain system and further exploiting the value of products. However, the implementation of reverse logistics is a long-term, complex and dynamic process. Many factors need to be considered by the stakeholders when making decisions. With the help of the evolutionary game approach, this paper establishes a model based on the relationship between the government, enterprises (manufacturing enterprises) and logistics companies, and conducts simulation analysis to provide references for how the three parties implement or participate in reverse logistics. The results of the study show that: 1) The total amount of waste affects the evolutionary direction of enterprises’ decision choices, while the conversion rate of waste has a significant impact on the evolutionary trajectory (speed) of enterprises’ decision choices. 2) When the government’s regulation and punishment of the implementation of reverse logistics is greater, enterprises can choose to implement outsourcing reverse logistics to transfer the risk. 3) Logistics companies give certain discounts to attract enterprises to cooperate with them, but excessive discounts have different degrees of negative impact on the normal operation of both enterprises and logistics companies.